Effect of sparing S1 motion segment on spinopelvic-sagittal balance relationship and its impact on pain and functional outcome - Mahmoud Saad; Ali A. Mowafy; Ahmed Naguib Taha; Ahmed R. Shalaby; Mostafa Shahein; Hanee Ali (Romanian Neurosurgery)
Purpose: To assess the effect of S1 motion segment sparing in the setting of degenerative spondylosis and its effect on spinopelvic-sagittal balance parameters and long-term pain and disability using VAS (visual analogue scale) and ODI (modified Oswestry disability index-Arabic version).